A comprehensive overview of jute fiber reinforced cementitious composites. (December 2021) - Song, Hongwei; Liu, Jing; He, Kaiyu; Ahmad, Waqas
Abstract: Natural fibers are eco-friendly, cost-effective, lightweight, renewable, have better thermal properties and corrosion resistance capabilities. The addition of natural fibers in cementitious composites (CCs) will be a sustainable step to enhance their mechanical properties as well as encouraging green construction. Jute fibers are cheap among all the natural fibers and are abundantly available in several developing countries. This study describes the impact of utilizing jute fibers in CCs for sustainable construction. The influence of jute fiber on the mechanical strength of CCs is reported, including compressive strength, split tensile strength, flexural strength. Additionally, the microstructure of jute fiber is discussed, and jute fiber-matrix interaction is explained. The effect of varying jute fiber length and content on the mechanical strength of CCs has been described, and optimum jute fiber length and content have been reported. The current research initiative expects to promote understanding of the concerns and difficulties encountered during the production of jute fiber reinforced CCs. It was concluded that incorporating jute fibers can enhance the strength properties of CCs if used in shorter lengths and lower volume contents, while higher volume content of jute fibers degraded the strength properties of CCs. In addition, the current research is quite limited in terms of practical applications of jute fiber reinforced CCs, and more research is needed in the future to determine their applications in civil engineering construction. Future research has been recommended in light of the different parameters discussed in this study. Moreover, this review will be helpful in promoting the use of jute fiber for the green construction of CCs.